Die 'evangelie' van Paulus - Aarde, Andries van (Verbum et ecclesia, 2002)
The 'gospel' of Paul This article focuses on Paul’s use of the term 'gospel'. It argues that the 'gospel of Christ' is God’s power for the recreation of humankind. Paul is Christ’s apostle who is sent to proclaim this message. The message is the 'gospel of God' and its proclamation is God’s dynamic act of recreation. The 'truth' of the gospel is that people do not need to seek salvation in anything transient. According to Paul, such a view is sin. A 'material relationship' exists between Paul’s 'gospel' and the historical Jesus’ 'subversive wisdom' which he expressed through his sayings and deeds. The center of the gospel is that God sends Jesus who, through his death and resurrection, terminates the old dispensation and inaugurates the new. However, the historical Jesus did not see his own death as God’s act of terminating the sinful dispensation. The reaction required by the 'gospel'of Paul is to accept and live by it. Paul calls this commitment 'faith'.